Marketing e qualidade em serviços de consultoria: uma aplicação da escala SERVQUAL - Rocha, Cicero Luis Carvalho (2007)
This work has as research question “How the evaluation of constructo quality is made by the customer of management consulting, in the perspective of the marketing and the quality?”. Using the model of the Servqual system (Parasuraman) and its 21 factors of quality, adapted these same factors for the services of management consulting, applying itself by means of survey (survey), with the controllers of the population of nine companies object of the study, crossing themselves qualitative sources of information and analyses, where if it proved that: a) the quality of the services of management consulting impact in the process of marketing of this service; b) the satisfaction of the customer of management consulting is constructed from a made up of four periods of training - the attributes, the consequences, the perception of value of the customer and the satisfaction of the customer; c) the expectations and the perceptions that the consuming customer of management consulting has of the quality of the services are a multidimensional concept; d) exists an Excellency standard, in the expectations of quality of the customers, regarding excellent factors in the attainment of a service of quality of management consulting. This study also it identifies to the relation between the quality and the process of marketing in the services of management consulting, the dimensions of expectation and perception that the customer-consumer of management consulting uses to evaluate the quality of the services and verifies the importance of the factors that the customers judge excellent in the attainment of a service of quality of management consulting. Another important conclusion of this study is that the type of consulting boarding has a significant relevance on the results of quality and the marketing of the consulting companies. This conclusion was formulated through the analysis of the results of the surveys, crossing them with the twelve searched models.